The Role of Communication and Work Environment on Employee Performance (Case Study: Boeing/Ethiopian Airlines 2019) - Zebua, Ovan Krisadelman; Sihaloho, Cristine Natasia; Siahaan, Kevin Valensius; Destiyani, Suci; Anggiani, Eka; Togatorop, Yayang Fariana; Dalimunthe, Syairal Fahmy (Jurnal Multidisiplin Teknologi dan Arsitektur, 2024)
As social creatures, humans need good communication when interacting with others. As is the case in the work environment, the existence of good communication between employees enables them to carry out their duties following their respective procedures to achieve the goals set by the agency or work organization. This research uses the literature study method. A literature study is a collection of previous research results in the form of books, articles, scientific journals, research  reports, and other sources relevant to the topic of discussion which are then compared theoretically. The Ethiopian Airlines Flight 302 incident highlighted several issues related to Boeing employee communication, work environment, and employee performance. Based on the case study discussed, this incident shows that to improve aviation safety, more attention needs to be paid to communication, work environment, and employee training in the aviation industry to prevent similar incidents from happening in the future.